2019
DOI: 10.1016/j.cell.2019.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of Subcellular RNA Localization Revealed by APEX-Seq

Abstract: Highlights d A transcriptome-wide subcellular RNA atlas was generated by proximity labeling d Isoform-level subcellular localization patterns for over 3,200 genes identified d RNA-transcript location correlates with genome architecture and protein localization d Two modes of mRNA localization to the outer mitochondrial membrane uncovered

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
436
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(495 citation statements)
references
References 125 publications
29
436
2
Order By: Relevance
“…Although the retained introns are predicted to undergo NMD, we found the retained intron transcripts to be NMD-insensitive. Instead we find they could be detained in the nucleus (Boutz, Bhutkar, and Sharp 2015) , a phenomenon also observed in a recent study on RNA localisation within different cellular compartments (Fazal et al 2018) ( Figure 8 ).…”
Section: The Comparisons Between the Joint Analysis Of Fus Mutationssupporting
confidence: 86%
“…Although the retained introns are predicted to undergo NMD, we found the retained intron transcripts to be NMD-insensitive. Instead we find they could be detained in the nucleus (Boutz, Bhutkar, and Sharp 2015) , a phenomenon also observed in a recent study on RNA localisation within different cellular compartments (Fazal et al 2018) ( Figure 8 ).…”
Section: The Comparisons Between the Joint Analysis Of Fus Mutationssupporting
confidence: 86%
“…Additionally, we observed no detectable diffusion of biotinylated material outside of the nucleus in our live-cell APEX label and chase experiments ( Figure S1D), which further support the idea that the APEX labeling captured the NL-associated RNAs. We found that previously identified mRNA transcripts with retained introns in the nuclear and APEX-RIP samples which are then mostly, but not completely removed in the cytosolic RNA-seq fraction ( Figure S2D, black bars) (Boutz et al, 2015;Fazal et al, 2019;Lareau et al, 2007).…”
Section: Apex2-lamin-b1 Labeling Identifies Nl-associated Rna With Lomentioning
confidence: 80%
“…Previous studies have used the APEX procedure to isolate RNAs (APEX-RIP) associated with cellular organelles and structures. This APEX-RIP procedure can be done by precipitating protein/RNA complexes, or by directly precipitating RNA since the APEX reaction will label RNA (Fazal et al, 2019;Kaewsapsak et al, 2017). In our experiments, we chose to precipitate protein/RNA complexes in order to isolate NLenriched RNAs since this is expected to yield a more extensive dataset.…”
Section: Apex2-lamin-b1 Labeling Identifies Nl-associated Rna With Lomentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1970s, electron microscopy analysis found that cytoplasmic ribosomes can be localized along the mitochondrial outer membrane (Kellems et al, 1974). Recent microarray and RNA-seq analyses of biochemically fractionated mitochondrial membranes and fluorescent microscopy analysis have identified subsets of nuclear-encoded mRNAs that are mitochondrially localized (Fazal et al, 2019;Gadir et al, 2011;Garcia et al, 2007;Marc et al, 2002;Saint-Georges et al, 2008;Williams et al, 2014). It has been shown that both the 3′ UTR and coding regions, primarily through mitochondrial targeting sequences (MTSs), contribute to mitochondrial localization.…”
Section: Introductionmentioning
confidence: 99%